DESIGN AND DEVELOPMENT OF 51 LEVEL NON MODULAR MULTILEVEL INVERTER TOPOLOGY WITH REDUCED NUMBER OF SWITCHES AND CONDUCTION PATH - S.Priyadharsini,; C.Kannan,; Ganesh Babu ,; C.Savithri,; K.Thamayandhi, (EPRA International Journal of Research and Development (IJRD), 2022)
In this paper, a 51 level multilevel inverter topology with non modular design is developed, which can be operated in asymmetrical mode with a reduced number of power switches and lesser conduction path. The proposed design has three separated DC sources and eleven active power switches, i.e., ten unidirectional switch and one bidirectional switch. The topology can be used with asymmetrical voltage source configuration to generate fifty one levels. This structure can be cascaded to produce maximum level by a series connection to produce higher voltage levels with less voltage stress on the switches without modifying the topology structure. A detailed Comparison is made with existing topology and recently introduced topologies based on the number of active switches, Separated DC sources, number of gate driver circuits. To prove the presented topology's superiority, a simple Multicarrier pulse width modulation has been deployed as the switching scheme. Validation on the viability of the proposed topology has been carried out through Matlab/Simulink simulation.